A novel treatment approach for a patient with advanced low rectal cancer: A case report and literature review. Issue 14 (7th April 2023) - Jiang, Xuejun; Zhou, Feng; Yuan, Fangjun; Lei, Xinyi; Liu, Cui; Ji, Zujin
Abstract : Rationale: In the treatment of low rectal cancer (LRC), preserving the anal sphincter is increasingly attracting the attention of colorectal surgeons. Many patients refused to perform a colostomy. Here, we report a case of LRC in a middle-aged woman and the clinical implications of the symptom, the treatment process of LRC, and the complications. Patient concerns: A 46-year-old woman visited our department with a tumor found on her physical examination because of hemafecia. Then she refused to perform abdominoperineal resection. Diagnosis: The patient first completed a colonoscopy and then underwent a rectal biopsy. The tumor was diagnosed as a rectal adenocarcinoma after pathological evaluation. Then it was staged by magnetic resonance imaging and enhanced computed X-ray tomography. Interventions: The treatment consisted of chemoradiotherapy followed by cryoablation. Outcomes: The patient achieved a good oncological outcome and preserved the sphincter successfully. The post-cryoablation course of the patient was uneventful and he remained healthy at the 1-year follow-up. Lessons: The preservation of anal sphincters has attracted more and more attention from colorectal surgeons. From the patient's perspective, the preservation of the anal sphincter was a key part of her treatment. We should try to meet the wishes of patients on the basis of curing the disease.